Menulis Karangan Argumentasi Dalam Pembelajaran Model Jigsaw-Elliot Aronson di SMK Multimedia Tumpang - Rokhyanto; Umi Salamah; Nurwakhid Muliyono (Universitas Insan Budi Utomo, 2026)
This research was motivated by the need to improve the argumentative writing skills of students at SMK Multimedia Tumpang. Writing is an activity that requires active and creative thinking. A model that can foster this activity and creativity is the jigsaw cooperative learning method. The jigsaw technique emphasizes collaboration, focusing on learning in small groups of four to six students, whose members are selected heterogeneously. Students work together in a positive, interdependent manner and assume independent responsibility. The method used in this research was a quasi-experimental method, with a trial of the jigsaw cooperative learning method in teaching paragraph writing for argumentative essays. The results of the study demonstrate that the jigsaw learning model is effective in teaching argumentative essay writing. This model can also improve the argumentative writing skills of SMK Multimedia Tumpang students.